2017
DOI: 10.4149/neo_2017_620
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the most common polymorphisms in TYMS gene in Slavic population of central Europe

Abstract: Thymidylate synthetase (TS) plays a critical role in the de novo synthesis of dTMP inside the cell. Therefore, TS is a suitable target for cytotoxic drugs such as fluoropyrimidines. Drug efficacy and toxicity depend on the intracellular level of TS, which is significantly influenced by the polymorphisms in the 5'UTR (TSER - rs45445694, TSER*3G>C - rs2853542) and 3'UTR (1494del TTAAAG - rs151264360) of TYMS gene. Polymorphic variants of TYMS gene affect TS activity via gene expression and transcript stability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies have shown that the homozygotes 3R/3R increase expression of TYMS mRNA when compared to cells in 2R/2R homozygotes (Kawakami et al, 1999). Another TYMS polymorphism, a 6-bp deletion/ insertion (TAAAGT) in the 3'-UTR (rs16430), has also been reported (Pastorakova et al, 2017;Marsh, 2005). Polymorphisms in the TYMS gene can affect the expression and stability of mRNA, and therefore affect protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the homozygotes 3R/3R increase expression of TYMS mRNA when compared to cells in 2R/2R homozygotes (Kawakami et al, 1999). Another TYMS polymorphism, a 6-bp deletion/ insertion (TAAAGT) in the 3'-UTR (rs16430), has also been reported (Pastorakova et al, 2017;Marsh, 2005). Polymorphisms in the TYMS gene can affect the expression and stability of mRNA, and therefore affect protein expression.…”
Section: Introductionmentioning
confidence: 99%